Unleashing potential and optimizing adolescent roller skating performance through a structured exercise program - a randomized controlled trial - Sehgal, S.; Chahal, A.; Esht, V.; Alshehri, M. M.; Beg, R. A.; Shaphe, M. A.; Alajam, R. A.; Kashoo, F. Z.; Alghadir, A. H.; Khan, M. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The intricate nature of an athlete's abilities evolves dynamically with the enhancement of motor skills. Hence the study sought to investigate the impact of a tailored four-week exercise program`encompassing exercises focused on balance, agility, and speed. The primary objective was to determine how this exercise program influences both the roller skating talent and overall physical fitness proficiency in young male roller skaters.